Bibliometric Analysis of Green Economy Learning for Children (1996-2023): Current Status and Future Directions - Utami, Nunung Nurastuti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research aims to map research conducted by reputable journals indexed by Scopus on Science Direct from 1996 to 2023 regarding the theme